Evaluation of intra‐group optimistic data replication in P2P groupware systems. (2nd April 2012) - Xhafa, Fatos; Potlog, Alina‐Diana; Spaho, Evjola; Pop, Florin; Cristea, Valentin; Barolli, Leonard; Hussain, Farookh Khadeer; Wyrzykowski, Roman; Tudruj, Marek
Summary Peer‐to‐peer (P2P) computing systems have become very popular during the last years because of their ability to scale to a large number of users and efficient communication among peers. They can support complex computational processes, beyond simple file sharing, while offering advantages of decentralized distributed systems. However, such systems may suffer from availability and reliability. To increase availability and reliability, and therefore, improve the perception of peers, yielding to fast response times and rich experience, data replication techniques are the foremost means in such systems. Indeed, in many P2P applications, for example, in a groupware, documents generated along application life cycle can change over time. The need is then to efficiently replicate dynamic documents and data to support group processes and collaboration. In this paper, we propose a replication system for documents structured as XML files and evaluate it under different scenarios. The proposed system has a super‐peer architecture that provides fast consistency for late joining peers. It uses optimistic replication techniques with propagating update operations from source to destination node in push mode. The system is suitable for asynchronous collaboration in online collaborative teams accomplishing a common project in a P2P environment. Copyright © 2012 John Wiley & Sons, Ltd.